Hypothesis: Ran GTPase-Based Potential Therapeutic Interventions Against Lethal Microbial Infections - Peter M.C. Wong (The Scientific World Journal)
Host innate immune response represents a vital immediate defense against infections by a diverse group of microorganisms that include bacteria, viruses, and fungi. Many types of cell surface receptors in mammalian cells specifically recognize particular groups of microorganisms and transmit response signals to the nuclei via multiple signal transduction pathways. These signaling pathways must merge at some point and are likely to be redundant, as the host innate immune response to many microorganisms is remarkably similar; it is characterized by the production of proinflammatory cytokines such as TNFα, IL-1, and IL-6 by the principal cell types – macrophages and dendritic cells. Since these cytokines influence greatly the magnitude of the cascade of inflammatory events, the proportion and the actual amount of each among the cytokine group may be a characteristic of each type of infections. Immune modulation by systematically up-regulate or down-modulate these cytokines would conceivably have major therapeutic potential. We have recently shown that two alleles of Ran cDNAs – RanT/n and RanC/d – may possess these characteristics. Thus the applica-tion of Ran to the treatment of septic shock, lethal anthrax shock, or adenovirus-induced toxicities may open up many interesting possibilities in the future.